Early piriform sinus cancer - results of treatment with partial vertical pharyngectomy - Élö, János (Radiology and oncology (Ljubljana), 1997)
Between 1986-1995, 179 patients with hypopharyngeal carcinoma were surgically treated at our department. Among them, 35 had functional partial resection. Out of these, 13 patients had vertical partial pharyngolaryngectomy carried out after ipsilateral neck dissection. The access to the primary tumors was made via lateral pharyngectomy. Eight out of thirteen patients aredisease freetwo after the treatment, with well functioning larynx. Some complications occurred, but there were no cases of surgery related death. The hypopharyngealcancers are considered as supermalignant tumors. The achieved good functional results and survival rate prove that conservation surgery -partial laryngopharyngectomy - in selected cases of early hypopharynx carcinoma is a good altrnative to radical surgery.
Keywords: Hypopharyngeal neoplasms; Methods; Pharyngectomy; Surgery; Treatment outcome